2012
DOI: 10.1038/modpathol.2012.43
|View full text |Cite
|
Sign up to set email alerts
|

Immune response in melanoma: an in-depth analysis of the primary tumor and corresponding sentinel lymph node

Abstract: The sentinel lymph node is the initial site of metastasis. Down-regulation of anti-tumor immunity plays a role in nodal progression. Our objective was to investigate the relationship between immune modulation and sentinel lymph node positivity, correlating it with outcome in melanoma patients. Lymph node/primary tissues from melanoma patients prospectively accrued and followed at New York University Medical Center were evaluated for the presence of regulatory T-cells (Foxp3+) and dendritic cells (conventional:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 35 publications
5
67
4
1
Order By: Relevance
“…This is the first study to analyze whole-genome gene expression profiling in SNB samples. Broad defects affecting different immunologic components have been extensively documented in SNs with respect to nontumor-draining nodes, including a decreased frequency of CD8 þ effector T cells, a reduced presence of stimulatory CD86 þ and CD11c þ DCs, and increased Foxp3 density and Th2 cytokine levels (7,11,(32)(33)(34)(35)(36)(37). Our findings partially contradict such observations because we found that immune dysfunction is detected in tumor-positive SNBs in association with disease progression.…”
Section: Discussioncontrasting
confidence: 57%
“…This is the first study to analyze whole-genome gene expression profiling in SNB samples. Broad defects affecting different immunologic components have been extensively documented in SNs with respect to nontumor-draining nodes, including a decreased frequency of CD8 þ effector T cells, a reduced presence of stimulatory CD86 þ and CD11c þ DCs, and increased Foxp3 density and Th2 cytokine levels (7,11,(32)(33)(34)(35)(36)(37). Our findings partially contradict such observations because we found that immune dysfunction is detected in tumor-positive SNBs in association with disease progression.…”
Section: Discussioncontrasting
confidence: 57%
“…Somatic immune indicators or molecular and cellular factors of immune response have been associated with melanoma progression, 92324 indicating that the balance of the immune repertoire (including tumour and effector T cell response, TILs or cytokine profiles) is important in modulating melanoma clinical outcomes. We hypothesise that genetic variation in the genes related to these processes may affect the immune capacity of the host.…”
Section: Discussionmentioning
confidence: 99%
“…56 A prospective study of Foxp3 + regulatory T cells and DCs in melanoma SNs showed correlations between node positivity and increased regulatory T cells or decreased dendritic cells. 57 Vallacchi et al, 58 using gene expression profiling of melanoma SNs and by unsupervised analysis of gene expression profiles, found "immune response" to be a major gene ontogeny represented.…”
Section: Evidence Of Sn Immune Modulation In Melanoma and Breast Cancermentioning
confidence: 98%